2012
DOI: 10.5296/ajfa.v4i1.1478
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Herding Behaviour in Indian Mutual Fund Industry

Abstract: The present study analyzes the trading activity of Indian mutual funds and investigates whether Indian mutual fund managers are engaged in herding behaviour. Results are compared with previous studies in mature as well as developing markets to determine the level of maturity of the Indian capital market. Measure of herding developed by Lakonishok et al. (1992) has been used. The study found strong evidence of herding in the overall sample. Managers herd primarily when they trade in large capitalization stocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The trading behaviour of mutual fund managers in India exhibit strong evidence of herding using LSV model and the study also showed herding behaviour is reflected in large capitalisation stocks as well as on big and famous stocks. The study found herding in Indian market is considered to be more when compared to other developed markets (Patro and Kanagaraj, 2012).…”
Section: Background Of the Studymentioning
confidence: 82%
“…The trading behaviour of mutual fund managers in India exhibit strong evidence of herding using LSV model and the study also showed herding behaviour is reflected in large capitalisation stocks as well as on big and famous stocks. The study found herding in Indian market is considered to be more when compared to other developed markets (Patro and Kanagaraj, 2012).…”
Section: Background Of the Studymentioning
confidence: 82%
“…Mutual fund herding for large capitalisation shares was more prominent in all periods than the small and medium capitalisation shares [44]. Fund managers herd more while purchasing a stock and trading voluminous stocks as compared to trading a stock [45]. The fund managers herd in order to safeguard their careers and get immunity in numbers.…”
Section: Herding and Mutual Fundsmentioning
confidence: 99%
“…Hung, Lu and Lee (2010) examined the herd behavior of mutual fund managers in Taiwan stock market, and they found that there is a tendency of herd behavior in that market. Patro and Kanagaraj (2012) analyzed the trading activity of Indian mutual funds and examined whether Indian mutual fund managers are engaged in herd behavior. As a result, they found strong evidence of herd behavior.…”
Section: Literature Reviewmentioning
confidence: 99%